Corporate Social Responsibility and Market Performance of Listed Companies in Sri Lanka - Thinusan, K.; Muraleetharan, P. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2024)
Corporate social responsibility (CSR) is the suggestion that businesses should function according to values and policies that create an optimistic impact on civilization and the surroundings. The study more identifies the leaning in CSR and market performance as well as the point of material particular by companies. This study utilized a sample of thirty publicly listed companies. CSR related data derived from the annual reports of thirty selected companies for the period of 2017 to 2022. The market performance feature of firm was evaluated using the Price Earnings Ratio (PER) and Earnings per Share (EPS). The result of the revision put additional that an inconsequential association exist among CSR and market performance of listed companies in Sri Lanka. Besides, support suggests where CSR exposure gives the impression of a slight development. The study also found that most of the information in annual reports focuses on CSR topics like employee relations, community involvement, environmental issues, product quality, and diversity. Additionally, the study suggests reducing unclearness surrounding the CSR on market performance impact and relationship in Sri Lanka; hence, scholars need to intensify studies in Sri Lankan viewpoint appreciably. Discussion is given additional into these findings along with paths for future research
Keywords: Corporate social responsibility; Earnings per share; Market performance